HCI International 2020 – Late Breaking Papers : Cognition, Learning and Games : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19–24, 2020, Proceedings /: Cognition, Learning and Games : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19–24, 2020, Proceedings. (2020) - Unknown
No abstract available